Spontaneous central venous thrombosis and shunt occlusion following peritoneovenous shunt placement for intractable ascites - Hariharan, D.; Wilkes, Emilie A.; Aithal, Guruprasad P.; Travis, S.J.; Lobo, Dileep N. (Royal College of Surgeons of England, 2017)
A 43-year-old man had a peritoneovenous shunt inserted for the treatment of chylous ascites secondary to myelofibrosis. Despite being on anticoagulation for superior mesenteric vein thrombosis, he developed shunt dysfunction within two weeks of insertion. Superior venacavography showed multiple filling defects in the right axillary vein, no filling of the right brachiocephalic and right subclavian vein, and thrombotic occlusion of the internal jugular veins bilaterally. The shunt was removed 11 days after insertion, and there was extensive thrombosis of the venous end of the shunt and the compressible pump chamber. Shunt thrombosis is known to occur but remains a rare complication, with 87% of such obstructions being due to a thrombus at the tip of the venous end of the shunt. Extensive thrombosis of the shunt (as in the present case) is very rare.